Risk factors of excessive daytime sleepiness in a prospective population‐based cohort. (15th May 2020) - Berger, Mathieu; Hirotsu, Camila; Haba‐Rubio, Jose; Betta, Monica; Bernardi, Giulio; Siclari, Francesca; Waeber, Gerard; Vollenweider, Peter; Marques‐Vidal, Pedro; Heinzer, Raphael
Summary: Although excessive daytime sleepiness is commonly evaluated in clinical and research settings using the Epworth Sleepiness Scale, few studies have assessed the factors associated with its incidence in the general population. We prospectively investigated the predictors of incident and persistent excessive daytime sleepiness in 2, 751 subjects (46.1% men, mean age 56.0 ± 9.8 years) from the CoLaus‐PsyCoLaus population‐based cohort (Lausanne, Switzerland) over 5 years. Participants completed the Epworth Sleepiness Scale and the Pittsburgh Sleep Quality Index, and underwent a full clinical evaluation at baseline and 5 years afterwards. Ambulatory polysomnography was performed at baseline in a sub‐sample of 1, 404 subjects. Among the 2, 438 subjects without excessive daytime sleepiness (Epworth Sleepiness Scale ≤ 10) at baseline, the 5‐year incidence of excessive daytime sleepiness was 5.1% ( n  = 124). Multivariate logistic regression revealed that male sex, depressive symptoms, reported poor sleep quality and moderate to severe obstructive sleep apnea were independent predictors of incident excessive daytime sleepiness, while older age, moderate coffee consumption, periodic leg movement during sleep and hypertension were independent protective factors. Stratified analysis according to sex and age showed some distinctive associations. Among the 313 patients with excessive daytime sleepiness at baseline, 137 (43.8%) had persistent excessive daytime sleepiness 5 years later. Our findings provide new insights into the predictors of incident excessive daytime sleepiness, but interventional studies are needed to understand the impact of treating these risk factors on the incidence of excessive daytime sleepiness.